TINKER STAYS HOME: STUDENT FREEDOM OF EXPRESSION IN VIRTUAL LEARNING PLATFORMS - Lawrence, Meghan K (Boston University law review, 2021)
Following the COVID-19 outbreak of March 2020, states imposed mandatory lockdowns, forcing schools throughout the country to move to virtual learning platforms. With this unprecedented shift came many unforeseen challenges for school officials, including assessing what First Amendment rights students retain in virtual learning platforms. Falling into an unusual gray area where students are technically in school because they are attending school-run classes, and yet off campus as they are doing so from the privacy of their homes, school officials have little guidance from the currently established student speech categories to make these determinations. While this issue originally arose out of the unique circumstances surrounding the COVID-19 pandemic, schools will likely continue to face this problem in the future, whether by the uncertain prospect of further school closings as new COVID-19 variants emerge or by schools and students continuing to take advantage of the convenience and safety provided by online platforms. This Note focuses on the intersection of existing student First Amendment rights both on and off campus and the constitutional protections afforded to speech and expression within the home. Ultimately, this Note concludes that there is no one-size-fits-all test that can be applied to all aspects of the virtual learning platform. While schools arguably must have some authority to limit student expression within virtual learning platforms, that authority must be balanced with students ' First Amendment rights. The two central problems posed by virtual learning platforms, virtual backgrounds and physical backgrounds, require a unique solution to balance protection of students ' rights and respect for a school 's authority. This Note argues that schools should wield far more authority over students' virtual backgrounds and less authority over their physical backgrounds. To control physical backgrounds, school officials must presume students are entitled to First Amendment protection over student expression subject to only few exceptions in specific categories of speech. Virtual backgrounds, on the other hand, do not exist outside of the virtual class, and thus do not implicate the same First Amendment and privacy concerns. This bifurcated solution thus accounts for the nature of virtual learning environments and balances school authority with not only students' First Amendment rights but also students' privacy rights, students' autonomy, and the authority of students ' parents to control their homelife.